2021
DOI: 10.34172/jlms.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of The Efficacy of Photobiomodulation and Ultrasound in the Treatment of Chronic Non-specific Neck Pain: A Randomized Single-Blind Controlled Trial

Abstract: Introduction: Chronic neck pain is a common complaint among office workers. The aim of the present study was to compare the efficacy of a high-intensity laser and physiotherapy in office workers who were diagnosed with chronic non-specific neck pain. Methods: This study was a single-blind randomized controlled trial, with parallel allocation. Sixty office workers with chronic neck pain, aged between 25 and 55 years, participated in the study. The participants were randomly divided into two groups: photobiomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
1
0
5
Order By: Relevance
“…Com uma taxa de desistência de 15%, foram calculadas 22 amostras em cada grupo, para um tamanho total de amostra de 44. 9 Os pacientes foram separados aleatoriamente em dois grupos, ou seja, o grupo A do LASER e o grupo B da UST, por meio de um programa computadorizado na proporção de 1:1. Todos os participantes preencheram os dados demográficos e os dados sobre dor cervical.…”
Section: Medida De Resultado Primáriounclassified
See 3 more Smart Citations
“…Com uma taxa de desistência de 15%, foram calculadas 22 amostras em cada grupo, para um tamanho total de amostra de 44. 9 Os pacientes foram separados aleatoriamente em dois grupos, ou seja, o grupo A do LASER e o grupo B da UST, por meio de um programa computadorizado na proporção de 1:1. Todos os participantes preencheram os dados demográficos e os dados sobre dor cervical.…”
Section: Medida De Resultado Primáriounclassified
“…No presente estudo, houve diferenças significativas nos valores de VAS, IIP e PPT no grupo LASER em comparação com o grupo UST. Os achados de nosso estudo são semelhantes aos do estudo de Kenarah et al 9 Uma revisão sistemática recente mostrou que a terapia a laser de alta intensidade é eficaz no tratamento de síndromes de dor miofascial do trapézio, dor miofascial cervical e pontos de gatilho. 16 Outra revisão sistemática também mostrou a eficácia do HILT no tratamento de condições musculoesqueléticas como fáscia plantar, OA graus 2-3, síndrome do túnel do carpelo, epicondilite lateral e dor lombar crônica.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In study by Kenareh, et al with 60 office workers, aged 25 until 55 years, showed the result that physiotherapy and photobiomodulation both help to lessen the various components of persistent neck pain, however laser treatment had a far greater impact than physiotherapy. 10 Yilmaz, et al did study of total 40 patients which is 22 women an 18 men that affected with cervical disc herniation and feel the neck pain showed that by lowering discomfort, it was discovered that the HILT plus exercise program and the TENS / US plus exercise program both improved cervical range of motion and quality of life. These two treatment plans can be used interchangeably in clinical settings and have comparable results when treating cervical pain brought on by CDH.…”
Section: Discussionmentioning
confidence: 99%